An Aminobutyric Acid Transaminase in Zea mays Interacts With Rhizoctonia solani Cellulase to Participate in Disease Resistance - Guo, Xiuna; Chen, Jinyin; Gao, Mengyi; Li, Duochuan (Frontiers in Plant Science, 2022)
Corn sheath blight, caused by AG1-IA, a fusion group of Rhizoctonia solani, which acts as a kind of necrotrophic fungal pathogen, poses a global threat to the production of Zea mays. Although cellulase plays a crucial role in R. solani infections, how plants respond to it is still poorly understood. In this study, we identified a gamma-aminobutyric acid transaminase (GABA-T), ZmGABA-T, in Z. mays that interacts with a cell wall–degrading enzyme (CWDE), EG1, in the cell membrane, using yeast two-hybrid assay, co-immunoprecipitation (Co-IP), and bimolecular fluorescence complementation assays. We found that the combination of EG1 and ZmGABA-T suppressed the allergic necrosis induced by EG1. We also found that the substrate of GABA-T–GABA, can inhibit the transcription of EG1. Transient expression of ZmGABA-T inhibited R. solani infection in Nicotiana benthamiana. The homolog in Oryza sativa, OsGABA-T, could also interact with EG1 to suppress the allergic necrosis induced by EG1. The OsGABA-T knocked out plants displayed enhanced susceptibility to R. solani and showed larger lesions. In conclusion, our results suggest that ZmGABA-T inhibits allergic necrosis induced by EG1 based on the combination with EG1, producing resistance to R. solani infection.